Earnings discontinuity as the proxy for earnings management: Empirical study from the UK, Germany and the Czech Republic - Jan Svitlík; Marcela Zárybnická Žárová (European Financial and Accounting Journal, 2019)
The paper deals with the phenomenon of earnings discontinuity around zero level in the UK, as the common law representative, Germany, as the civil law representative, and the Czech Republic, as the civil law representative where earnings management research has not yet been thoroughly realized. We undertake both cross-sectional and time-series analysis from 2006 to 2013. According to our findings, the UK is a low-earnings-management country with slightly decreasing trend of the earnings management level. On the other hand, earnings management engagement in Germany and the Czech Republic is of a significantly higher level than in the UK. Moreover, Czech companies suggest an increasing trend of the earnings management level. We find significant difference between the common law representative and the civil law ones in terms of the earnings management level.
Keywords: M41; 650; Czech Republic; Earnings Discontinuity; Earnings Management; Germany; United Kingdom